Religion as capital: Christianity in the lives of Anglo-Indian youth in India - Andrews, Robyn (Journal of contemporary religion, 2017)
Religion is an important marker of identity for India's Anglo-Indians. It distinguishes them within the principally non-Christian context and is integral to socializing youth to their distinct Anglo-Indian culture and heritage. This can be observed in Anglo-Indian practiceattending Christian schools, church-going, celebrating religious festivals, making pilgrimageswhich forms a significant part of a matrix through which young Anglo-Indians learn how to perform their Anglo-Indianness. Our recent research (2013-2014) looked at the role of religion in the lives of Anglo-Indians intergenerationally and transnationally, through a survey, interviews, and participant observation. The results suggest that the performed religiosity of Anglo-Indian youth in India yields certain benefits for this group. It constitutes a capital which has the potential to make an enormous difference to their livessocially, culturally, and otherwise. For example, Christian practice provides them with access to élite Christian educational institutions and the career possibilities that follow from such education. This article describes our research, focusing upon the findings related to Anglo-Indian youth in India. In particular, it argues that in various ways, the practice of Christianity both acts and is recognized by young Anglo-Indians as a source of capital in their lives, which is not to say that religion is practised for the purpose of acquiring capital. Rather, religious practice is a part of being Anglo-Indian that in India accrues capital.